2021
DOI: 10.3390/su13179776
|View full text |Cite
|
Sign up to set email alerts
|

Development of Virtual Reality Automotive Lab for Training in Engineering Students

Abstract: A Virtual Reality application was developed to be used as an immersive virtual learning strategy for Oculus Rift S Virtual Reality glasses and through Leap Motion Controller™ infrared sensors, focused on students of the Automotive Systems Engineering academic program, as a practical teaching-learning tool in the context of Education 4.0 and the pandemic caused by COVID-19 that has kept schools closed since March 2020. The technological pillars of Industry 4.0 were used to profile students so that they can meet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 53 publications
0
9
0
1
Order By: Relevance
“…Unfortunately, safety training delivering information through the abovementioned procedure usually offers a low level of engagement, presence, as well as realism since it is difficult for the new employees to fully visualize and understand the information provided from 2D pictures and text (Numfu et al, 2020). To bridge these gaps, several researchers developed VR-based machinery and/or process operation safety training in construction (Beh et al, 2021;Choi et al, 2020;Guo et al, 2012;Li et al, 2012;Osti et al, 2021;Shi et al, 2020;Song et al, 2021;Vahdatikhaki et al, 2019;Wang et al, 2020), manufacturing and assembly (Dado et al, 2018;Gallegos-Nieto et al, 2017;Grandi et al, 2021;Hernández-Chávez et al, 2021;Numfu et al, 2020;Serpa et al, 2020), electric power and electronics (Ayala García et al, 2016;Ogbuanya & Onele, 2018), and agriculture (Ojados Gonzalez et al, 2017) as shown in Fig. 4.…”
Section: What Topics Have Researchers Investigated For Vr-based Healt...mentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, safety training delivering information through the abovementioned procedure usually offers a low level of engagement, presence, as well as realism since it is difficult for the new employees to fully visualize and understand the information provided from 2D pictures and text (Numfu et al, 2020). To bridge these gaps, several researchers developed VR-based machinery and/or process operation safety training in construction (Beh et al, 2021;Choi et al, 2020;Guo et al, 2012;Li et al, 2012;Osti et al, 2021;Shi et al, 2020;Song et al, 2021;Vahdatikhaki et al, 2019;Wang et al, 2020), manufacturing and assembly (Dado et al, 2018;Gallegos-Nieto et al, 2017;Grandi et al, 2021;Hernández-Chávez et al, 2021;Numfu et al, 2020;Serpa et al, 2020), electric power and electronics (Ayala García et al, 2016;Ogbuanya & Onele, 2018), and agriculture (Ojados Gonzalez et al, 2017) as shown in Fig. 4.…”
Section: What Topics Have Researchers Investigated For Vr-based Healt...mentioning
confidence: 99%
“…Moreover, two of the papers compared the reaction level of different types of VR-based training system. For instance, Hernández-Chávez et al (2021) and Dhalmahapatra et al (2021) compared the reaction level between fully immersive VR and non-immersive VR. Both of their results showed that the fully immersive VR was better with respect to several reaction level criteria such as ease of operation, ease of learning, realism, immersion, and/ or graphics quality compared to desktop VR.…”
Section: Does Vr-based Health and Safety Training In Various High-ris...mentioning
confidence: 99%
“…Furthermore, the 3D image is combined with the 3D Blender application to create a virtual object whose format follows the application on the game engine. This design used Unity 3D (Hernández-Chávez et al, 2021), a game engine, to create applications for this AR application based on android mobile (Södervik et al, 2021). Next is the marker on Vuforia.…”
Section: Figure 9 Ar Radar Design Stagesmentioning
confidence: 99%
“…The research conducted so far indicates that the user who is in an immersive environment effectively acquires knowledge [10,11]. Due to its advantages, VR technology is widely used in research [12][13][14][15][16], industrial [17][18][19][20][21][22] and educational [21,[23][24][25][26][27][28][29][30][31] areas. However, the literature review in this field in the case of existing solutions in Poland shows that this topic is quite new, and according to [23], we can see that there are not many Polish solutions that are widely used in the case of didactics at technical universities.…”
Section: Introductionmentioning
confidence: 99%